Detection of Entamoeba histolytica DNA in the Saliva of Amoebic Liver Abscess Patients Who Received Prior Treatment with Metronidazole (Journal of Health, Population and Nutrition, 2009)
Saliva is an easily-accessible and a non-invasive clinical specimen alternate to blood and liver pus. An atÂtempt was made to detect Entamoeba histolytica DNA released in the saliva of amoebic liver abscess (ALA) patients by applying 16S-like rRNA gene-based nested multiplex polymerase chain reaction (NM-PCR). The NM-PCR detected E. histolytica DNA in the saliva of eight (28.6%) of 28 ALA patients. The NM-PCR result was negative for E. histolytica DNA in the saliva of all the eight ALA patients who were tested prior to treatÂment with metronidazole but was positive in the saliva of eight (40%) of 20 ALA patient who were tested after therapy with metronidazole. The NM-PCR detected E. histolytica DNA in liver abscess pus of all 28 (100%) patients with ALA. The TechLab E. histolytica II enzyme-linked immunosorbent assay was positive for E. histolytica Gal/GalNAc lectin antigen in the liver abscess pus of 13 (46.4%) of the 28 ALA patients. The indirect haemagglutination (IHA) test was positive for anti-amoebic antibodies in the serum of 22 (78.6%) of the 28 ALA patients and 2 (5.7%) of 35 healthy controls. The present study, for the first time, demonstrates the release of E. histolytica DNA in the saliva of ALA patients by applying NM-PCR. Key words: Amoebiasis; DNA; Entamoeba histolytica; Metronidazole; Polymerase chain reaction; Saliva; India doi:10.3329/jhpn.v26i4.1883 J Health Popul Nutr 2008 Dec:26(4):418-425